Components of seed production and ergot resistance used as criteria for selection of Brachiaria hybrids - João José de Abreu Assumpção Demarchi (Acta Scientiarum. Animal Sciences, 2022)
Ergot is a fungal disease and causes reductions in seed productivity and quality. We aimed to identify promising genotypes of brachiaria evaluating: (1) seed production potential (number of tillers, racemes per inflorescence, spikelets per raceme, raceme length, weight and number of seeds, and germination) and (2) resistance of seeds to Ergot (infected tillers, infected seeds). Five genotypes of Brachiaria grasses, four non-natural hybrids named BH1619, BH1810, BH1516 and Mavuno Palisadegrass (Urochloa brizantha x Urochloa ruziziensis), and Marandu Palisadegrass (U. brizantha Hoechst cv. Marandu) were evaluated. The BH1619 hybrid, despite the high weight of seeds, produced less viable, pure seeds. The hybrid BH1516 had a lower percentage of flowered tillers (42%) and seeds infected with ergot (8%). Marandu Palisadegrass had a higher percentage of infected tillers (95%) and infected seeds (38%). The hybrid BH1516 was the most resistant to ergot, followed by Mavuno Palisadegras sand BH1619. Among all materials, Mavuno Palisadegrass and BH1516 have a higher potential for seed production due to the higher percentage of flowered tillers and production of pure seeds with high germination capacity. The BH1516 hybrid was resistant to ergot, making it a better choice for use in infected areas used for seed or forage production.